2018
DOI: 10.3390/polym10101114
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Polyphosphate Intercalated Layered Double Hydroxide and Zinc Borate as Highly Efficient Flame Retardant Nanofillers for Polypropylene

Abstract: We found in our previous study that layered double hydroxides (LDHs) which undergo aqueous miscible organic solvent treatment (AMOST) can tune the hydrophobicity surface of LDHs to be hydrophobic, and then the solvent mixing method can be used to prepare polymer/LDH nanocomposites. However, flame retardant property is not very high if LDHs are only used. In this present work, ammonium polyphosphate (APP) intercalated LDHs and zinc borate (ZB) was incorporated into a polypropylene (PP) matrix using the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…These results were compatible with the composition of the F3 formulation used for zirconia NPs, ammonium polyphosphate, boric acid, chitosan, and melamine. These results are in good agreement with previously reported results [52].…”
Section: Eds Analysissupporting
confidence: 94%
“…These results were compatible with the composition of the F3 formulation used for zirconia NPs, ammonium polyphosphate, boric acid, chitosan, and melamine. These results are in good agreement with previously reported results [52].…”
Section: Eds Analysissupporting
confidence: 94%
“…However, by mixing more than two FRs, a synergstic effect occurs and a strong char layer is formed during the burning process. Gao, Y. et al (2018) have investigated the flame retardancy of PP treated with ammonium phosphate (APP) intercalated LDHs and zinc borate (ZB) and 10 wt.% of APP-LDH combined with 2 wt.% of ZB decreased PHRR for 42% compared to pristine PP [ 163 ]. A paper published by Xu, S. et al (2020) [ 159 ] showed much higher nanofiller loading due to the usage of FR complex made of hydrotalcite LDH intercalated with sodium alginate (SA) into its interlayer space followed by melt blending with a PP polymer.…”
Section: Flame Retardant Chemistrymentioning
confidence: 99%
“…LDHs have been used as acid scavengers [ 17 ], in the pharmaceutical industry [ 18 ], as antioxidants [ 19 ], in biomedical applications [ 20 , 21 , 22 , 23 ], as UV-Vis absorption materials [ 12 , 24 , 25 , 26 ], in photovoltaic and solar cells [ 26 ], in supercapacitors [ 27 ], in sensors [ 28 ], in wastewater treatments [ 29 ], as precursors for photocatalytic materials [ 30 , 31 ], as catalysts [ 18 , 32 ], as stabilizers in polymers [ 33 , 34 ] and as flame retardants for polymers [ 35 , 36 , 37 , 38 ]. LDHs can be used for different purposes—as coolants and in producing diluents for flammable gas [ 39 ], as flame retardants providing resistance to ignition [ 40 ], or they can provide an alternate way of combustion with a slower rate of flame spread and can reduce the quantity of smoke [ 18 , 40 ].…”
Section: Introductionmentioning
confidence: 99%